Faktor-Faktor Resiko Stunting Anak Usia Pra Sekolah di Wilayah Bencana Erupsi Gunung Berapi - Abiddin, Andi Hayyun; Anam, Agus Khoirul (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Natural disasters are events that cause loss of property, environmental damage, damage to infrastructure, and even loss of life. One of the disaster threats in Indonesia is volcanic eruptions which cause poverty, affecting family investments in children's nutrition and health care. To identify risk factors for stunting in pre-school children in volcanic eruption disaster areas. This research design is cross-sectional. The sample in this study was kindergarten school students located in areas prone to volcanic eruptions, a total of 30 respondents taken using purposive sampling with inclusion criteria: (1) Kindergarten students A and B; (2) the school is located in an area prone to volcanic eruptions; (3) willing to be a respondent; and (4) the student is not suffering from a chronic, congenital disease or mental disorder. Respondents were excluded mothers who were unable to carry out interviews. The sample in this study was 30 respondents. Data were collected using a questionnaire prepared based on WHO guidelines and recommendations for feeding children from the Indonesian Pediatrician Association (IDAI). Data analysis used descriptive analysis and Chi Square test (p<0.05). The results showed that 3 subjects (10%) of the 30 total subjects belonged to the stunting group. The factors causing stunting that have a significant relationship with the incidence of stunting in the Argia Candi Sewu Kindergarten are maternal education (p-value 0.04), family income (p-value 0.01), and immunization history (p-value 0.02). The mother's role is very important, as the mother as a caregiver has all decisions regarding healthy feeding practices, including breastfeeding.  Keywords: Stunting, Pre-School Children, Disasters, Volcanoes  ABSTRAK Bencana alam merupakan peristiwa yang menimbulkan hilangnya harta benda, rusaknya lingkungan, rusaknya prasarana, bahkan hilangnya nyawa. Salah satu ancaman bencana di Indonesia adalah erupsi gunung berapi yang menyebabkan kemiskinan, memengaruhi investasi keluarga pada nutrisi dan perawatan kesehatan anak-anak. Mengidentifikasi faktor-faktor resiko stunting anak usia pra sekolah di wilayah bencana erupsi gunung berapi. Design penelitian ini cross-sectional. Sampel dalam penelitian ini adalah siswa sekolah TK yang berada di kawasan rawan bencana erupsi gunung berapi sejumlah 30 responden yang diambil menggunakan purposive sampling dengan kriteria inklusi: (1) siswa TK A dan B; (2) sekolah berada di Kawasan Rawan Bencana erupsi gunung berapi; (3) bersedia menjadi responden; dan (4) siswa tidak sedang menderita penyakit kronis, bawaan maupun gangguan mental. Responden yang dieksklusi ibu yang tidak dapat melakukan wawancara. Sampel dalam penelitian ini sebanyak 30 responden. Pengumpulan data menggunakan kuesioner yang disusun berdasarkan panduan WHO dan rekomendasi pemberian makan pada anak dari Ikatan Dokter Anak Indonesia (IDAI). Analisis data menggunakan deskriptif, dan uji Chi Square (p<0.05). Hasil penelitian menunjukkan bahwa 3 subjek (10%) dari 30 total subjek termasuk kelompok stunting.  Faktor-faktor penyebab stunting yang memiliki hubungan bermakna dengan  kejadian  stunting di TK Argia Candi Sewu adalah pendidikan ibu (p-value 0,04),   penghasilan keluarga (p-value 0,01), dan riwayat imunisasi (p-value 0,02). Peran ibu sangat penting, seperti Ibu sebagai pengasuh mempunyai segala keputusan tentang praktik pemberian makan yang sehat, termasuk menyusui. Kata Kunci: Stunting, Anak Usia Pra Sekolah, Bencana, Gunung Berapi